Redes sociais e migrações laborais: múltiplas territorialidades. A constituição da rede nipo-brasileira em Ourinhos (SP) e no Japão - Melchior, Lirian [UNESP] (2008)
The labor mobility, imposed by production capitalistic relations, reinforces the feeling of belonging to the place of origin, (re)creating identity relations in the most varied places where the migrants go to. The process of area (territory) formation with specific characteristics of a social group from ethnic or regional origins, enabled by the social nets, faces the homogenizing tendencies of globalization, highlighting hybrid cultural spaces. This phenomenon was studied based on the Japanese migration to Brazil – Ourinhos (SP) – and on their descendants to Japan, aiming to understand the different territorial conformities and spatial arrangements, materialized in the urban area, and it was concluded that the social nets find themselves subordinate to the interests of hegemonic economic agents and they are essential elements to the accomplishment of migratory processes.